Microemulsion-based hydrogel for topical delivery of indomethacin - Wantida Chaiyana (2018)
© 2015, International Journal of Pharmacy and Pharmaceutical Sciences. All rights reserved. Objective: The present study aims to develop and characterize microemulsion from herbal infused oil of Zingiber cassumunar (HO) and microemulsion-based hydrogel (MBH) containing indomethacin. The release patterns of indomethacin from MBH were also investigated. Methods: HO was produced by hot extraction of Z. cassumunar rhizome in coconut oil, and characterized for acid value, iodine value, and saponification value. The cytotoxicity of HO on human peripheral blood mononucleared cells (PBMCs) was also investigated. Pseudoternary phase diagram was constructed to study suitable compositions of microemulsion containing HO, oleic acid, Triton X-114, propan-2-ol, and water. Indomethacin was then incorporated into the microemulsion and finally blended with gel base (2% Carbopol 940 or 3% sodium carboxymethylcellulose) to produce MBH. The indomethacin MBH was characterized for appearance, pH, viscosity, and in vitro release characteristics. Results: HO exhibited an acid value of 0.203 ± 0.004 mg of KOH/g, iodine value of 7.39 ± 0.15 g of I2/100 g, and saponification value of 265.4 ± 7.3 mg of KOH/g with no cytotoxic effect on human PBMCs. The microemulsion region in the pseudoternary phase diagram of HO, oleic acid, Triton X-114, propan-2-ol, and water was 45.25%. Six microemulsions (ME1– ME6) containing 10% of HO and oleic acid mixture (1:1) as the oil phase and Triton X-114 and propan-2-ol (3:2) as surfactant mixture were formulated and characterized. The droplet size was in the range of 26 to 32 nm with polydispersity index less than 0.3. They showed a Newtonian flow behavior with the viscosity ranging from 15.12 ± 0.15 to 16.78 ± 0.12 Pas. The microemulsion was incorporated into hydrogel using 3% sodium carboxymethylcellulose or 2% Carbopol 940. Only ME1 – ME3 gave clear MBH; therefore, they were studied in the in vitrorelease of indomethacin, and the results indicated the sustained-release characteristic fitted the Higuchi model. Conclusion: The topical MBH, containing microemulsion of HO, oleic acid, Triton X-114, propan-2-ol and water, might be a promising approach for sustained transdermal delivery of poor water-soluble compounds, including indomethacin.